(untitled) (Biological Sciences - PJSIR, 2002)
Physicochemical status of an industrial textile’s effiuent and its environment (soil and agricultural product-cas sava tubers) at Ado-Ekiti , Nigeria was assessed. Results showed that great variation existed among the parameters (pH units, tempera ture, conductivity, total hardness, total alkalinity, bicarbonate and hydroxide hardness, calcium and magnesium hardness, chloride and metal elements) down the channel , significant difference (P<0.05) existed among the minerals in the effiuent, soil sediments and cassava tubers in the three difterent zones. Fe, Mg, Ca, Na, K and Ni were found to be more concentrated in the effluent whereas Co, Zn , Cu, Pb, Cd and Mn were more concentrated in the soil sediments. However, Fe, Pb and Mn were more concentrated in the effluent than in cassava tubers. Mg, Ca, Zn,Cu, Cd, Na and K were more highly concentrated in cassava tubers showing evidence of bioaccumulation.